IDIOM DALAM FILM INFERNO KARYA RON HOWARD - DA CUNHA, YUVENCIA PRICILLIA FERLINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Idiom is an expression that contain of word, phrase or clause which have a frequent figurative language that is often used in speech.  the meaning of idiom is very different from literal meaning, it does not describe one of the word which is form it. Idiom has an important role in constructing formative sentences. This study focuses on idiomatic expressions used in Inferno movie. The foreigner students found many difficulties to understand the meaning of idiom by the native speaker English. The writer realizes that idiom is the one of the most important part in language  especially in English language. This reality encourages the writer to research the form and meaning of the idiom in Inferno movie. The aim of this research is to identify, classify, and analyze the idiom based on their forms and meanings. The descriptive method is used in this research, the data has been taken from the movie and analyzed them based on the theory Boatner and Gates. The results of this research shows that idioms can be found in various of idiom?s form. It is proved by the number of idioms form which was identified in the movie : There are 76 idioms that classified in 3 forms, 56 lexemic idioms, which are divided in 4 classes, 42 verbal idioms, 7 noun idioms, 1 adjective idiom, 6 adverb idioms, 19 phrases idioms, 2 proverbs.   Keyword : Idiom, form and meaning, Inferno